Monge–Ampère singular integral operators acting on Triebel–Lizorkin spaces. Issue 5 (4th April 2021) - Cheng, Meifang; Lee, Ming-Yi; Lin, Chin-Cheng; Qu, Meng
Abstract : We study the Triebel–Lizorkin spaces associated with sections which are closely related to the Monge-Ampère equations and show that Monge-Ampère singular integral operators are bounded on these Triebel–Lizorkin spaces.